Informational Externalities and Welfare-Reducing Speculation - Stein, Jeremy C. (Journal of Political Economy, 1987)
Introducing more speculators into the market for a given commodity leads to improved risk sharing but can also change the informational content of prices. This inflicts an externality on those traders already in the market, whose ability to make inferences based on current prices will be aff ected. In some cases, the externality is negative: the entry of new s peculators lowers the informativeness of the price to existing trader s. The net result can be one of price destabilization and welfare red uction. This is true even when all agents are rational, risk-averse c ompetitors who make the best possible use of their available informat ion. Copyright 1987 by University of Chicago Press.